The Preview, Question, Read, Summarize, and Test (PQRST) strategy and reading comprehension among middle basic education students at an educational institution in Loja, school year 2023-2024 - Brito Brito, Thalía Cecibel (2024)
Reading comprehension is a complex process that involves not only the accurate reading of words and sentences but also a deep understanding of vocabulary and general knowledge. Thus, this research aimed to describe the impact of the PQRST (Preview, Question, Read, Summarize, and Test) strategy on reading comprehension among middle basic education students in Loja during the 2023-2024 school year. The study used mixed method approach, incorporating both quantitative and qualitative data collection, and an action research design. To collect the data, a pre- and post-test were used in order to assess the students’ level regarding their reading comprehension before and after the intervention. Likewise, a questionnaire and field notes were used to describe the different opinions and behaviors of the students about the use of the strategy. These instruments were applied to seventh graders, who were sixteen girls and fourteen boys with an average age between eleven to twelve years old. For the analysis of the quantitative data, a descriptive analysis was used, while for the analysis of the qualitative data, a thematic analysis was used to then perform a triangulation of the instruments. The findings showed a notable difference between the pre- and post-tests, with an overall improvement of 1.7 points. Specifically, in the aspect of reading for gist, there was a difference of 0.05 points. In reading for specific information, there was a difference of 0.59 points, and in inferring meaning through text, there was a difference of 1.06 points. These results indicated that the PQRST strategy is an effective strategy for improving reading comprehension, as it motivated and engaged students, which suggested integrating the PQRST strategy into teaching practices to enhance reading comprehension and academic performance. Key words: Reading for gist, reading for specific information, inferring meaning, students’ perceptions.